2022
DOI: 10.3389/fpubh.2022.898556
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: A Source of Stress and Depression Among University Students and Poor Academic Performance

Abstract: Current research examines how COVID-19 has impacted the daily life of students, specifically personal and academic aspects. The authors investigated the role of academic and family stress caused by COVID-19 on students' depression levels and the subsequent impact on their academic performance based on Lazarus' cognitive appraisal theory of stress. The non-probability convenience sampling technique has been used to collect data from undergraduate and postgraduate students using a modified questionnaire with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…The results of this study revealed that the overall academic stress was associated with depression where the ndings are similar in previous studies (Alhamed, Results stress was associated signi cantly with depression among students (Jiang et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study revealed that the overall academic stress was associated with depression where the ndings are similar in previous studies (Alhamed, Results stress was associated signi cantly with depression among students (Jiang et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Opposite to the results of this study, university students who had a high GPA also had a high depression level. (Jiang et al, 2022) indicated that students must maintain their high GPA throughout their academic study because they were concerned about nding excellent jobs after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] The ASU strike and the COVID-19 Pandemic several waves are likely responsible for this trajectory increase in student depression. [13,14] The results of the chi-square test between the PHQ-9 score and gender showed a significant difference, which confirms the findings that men experience depression at a rate of 28% compared to 23% for women. [3] Female students were reported to have more depression than male students.…”
Section: Discussionsupporting
confidence: 78%
“…[ 10 , 11 ] COVID-19 pandemic resulted in worldwide shot down of educational institutions, sparked stress, anxiety, and worry about getting infected which increased the rate of depression in undergraduate students. [ 12 , 13 ] The pandemic caused students to experience a lot of academic stress which exacerbated their depression level. [ 13 ] With the implementation of shot down policy, physical classes were replaced with online classes, which came with their own set of challenges and annoyances due to the low digital literacy levels and lack of smart phones among the majority of the students, [ 14 ] as well as Nigeria problematic internet connection issues.…”
Section: Introductionmentioning
confidence: 99%
“…Depression has become widespread among university students and is understood as a critical barrier to academic performance at the university ( Jiang et al, 2022 , Wagner et al, 2022 ). Systematic reviews show that the occurrence of depressive symptoms is higher among university students than among non-college students or the general population ( Akhtar et al, 2020 , Luo et al, 2021 , Zou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%